(untitled) (Bangladesh Rice Journal, 2021)
Avenues of agronomic manipulation need to be explored critically for getting potential rice yield in a given environment. Increasing population, decreasing resources and increasing climate vulnerability such as salinity, drought, submergence, early flash flood in haor areas can interrupt achieving the target of rice yield. Location specific variety, profitable cropping sequences, innovative and smart cultural management, and appropriate agronomic management with smart dissemination using multiple means would maximize rice yield and decrease the production barriers of rice. Appropriate variety and location- specific crop management systems should be formulated for rice yield maximization to reduce yield gap in farmers’ field. A number of approaches can be undertaken for maximizing rice yield by adopting location-specific crop production e.g., manipulating sowing and planting times, appropriate weed management technology in proper time, suitable variety selection for improving cropping intensity, Judicious and balance application of organic and inorganic fertilizer application etc. Nitrogen application before panicle primordia is crucial because at this stage panicle primordia determined the spikelet number of the panicle and the absorbed nitrogen is efficiently used to increase spikelet number, accumulated photosynthates to leaf sheath and culm and, hence, increases panicle size and grain yield. Farmers should have a plan and should follow different steps of rice production to get higher yield and sustain productivity. Rice growth stage- wise agronomic management should be followed to get maximum yield. Choice of appropriate variety in a specific location or ecosystem is a major concern that contributed about 20% to the grain yield. Whereas management is a big issues which contributed about 60% for obtaining higher grain yield.The difference of environment × management explained the largest variations ( 80%) in explaining the yield. The bridging of knowledge gaps can bridge yield gaps. New paradigms need to be added to transfer and use new high yielding varieties and knowledge based technologies under new policy settings. Bangladesh Rice J. 24 (2): 161-181, 2021